JURIDICAL ANALYSIS OF THE IMPLEMENTATION OF ITSBAT NIKAH IN THE PRINCIPLE OF LEGAL CERTAINTY IN THE RELIGIOUS COURT DECISION NUMBER 93/PDT.P/2018/PA.TTE - Sukiati, Sukiati; Harahap, Yadi; Lubis, Indah Amani (PT. Altin Riset Publishing, 2024)
Underhand marriage or nikah siri has been an issue that has arisen in line with the enactment of Law No. 1/1974 on marriage in Indonesia. Nikah siri refers to a marriage that is not valid according to the applicable law, conducted outside the provisions of the Indonesian marriage law. Marriage, as a social institution, is a means to legitimize sexual relations between husband and wife and to ensure the continuation of human existence. However, nikah siri, which often takes place without parental or government notification, has significant negative legal implications for the parties involved, including non-recognition of the legal status of the wife, disenfranchisement from inheritance or property, and the absence of a formal mechanism for separation. Islamic law stipulates that a marriage is valid if it fulfills its pillars and conditions and no prohibitions are preventing it. In the context of positive law, every marriage must be recorded by applicable laws and regulations. However, the issue of marriage recognition through itsbat nikah in Islamic law creates complexity and the need for clear restrictions on its application. Therefore, official registration by authorized officials is important to maintain order in marriage and provide legal protection for the parties involved.